Variation in the Marking of Text Organization in French Research Articles: From Short and Specific to Extended and Vague - Veronika Laippala (Discours)
Adopting a text linguistic, corpus-based approach, this article studies variation in the marking of text organization. Why is text organization sometimes signaled very precisely, while sometimes signaling does not occur at all? The focus is on a particular mode of text organization, taking the form of text sequences, i.e. structures at least partially signaled by markers of addition or order, such as first, the last example. The material consists of 90 research articles in French with manually XML-annotated text sequences (XML = Extensible Markup Language). The results highlight the variation in the marking and show several factors affecting it. In shorter sequences, the marking is typically explicit and precise, while in longer ones explicit marking is more often omitted; when used, only vague markers, signaling simple addition, are present. In addition, different markers tend to be used in the signaling of sequences of different lengths.